MRI Analysis of White Matter Myelin Water Content in Multiple Sclerosis: A Novel Approach Applied to Finding Correlates of Cortical Thinning - Dayan, Michael; Hurtado Rúa, Sandra M.; Monohan, Elizabeth; Fujimoto, Kyoko; Pandya, Sneha; LoCastro, Eve M.; Vartanian, Tim; Nguyen, Thanh D.; Raj, Ashish; Gauthier, Susan A. (Frontiers in Neuroscience, 2017)
A novel lesion-mask free method based on a gamma mixture model was applied to myelin water fraction (MWF) maps to estimate the association between cortical thickness and myelin content, and how it differs between relapsing-remitting (RRMS) and secondary-progressive multiple sclerosis (SPMS) groups (135 and 23 patients respectively). It was compared to an approach based on lesion masks. The gamma mixture distribution of whole brain, white matter (WM) MWF was characterized with three variables: the mode (most frequent value) m1 of the gamma component shown to relate to lesion, the mode m2 of the component shown to be associated with normal appearing (NA) WM, and the mixing ratio (λ) between the two distributions. The lesion-mask approach relied on the mean MWF within lesion and within NAWM. A multivariate regression analysis was carried out to find the best predictors of cortical thickness for each group and for each approach. The gamma-mixture method was shown to outperform the lesion-mask approach in terms of adjusted R2, both for the RRMS and SPMS groups. The predictors of the final gamma-mixture models were found to be m1 (β=1.56, p<0.005), λ (β=−0.30, p<0.0005) and age (β=−0.0031, p<0.005) for the RRMS group (adjusted R2=0.16), and m2 (β=4.72, p<0.0005) for the SPMS group (adjusted R2=0.45). Further, a DICE coefficient analysis demonstrated that the lesion mask had more overlap to an ROI associated to m1 , than to an ROI associated to m2 (p < 0.00001), and vice versa for the NAWM mask (p < 0.00001). These results suggest that during the relapsing phase, focal WM damage is associated with cortical thinning, yet in SPMS patients, global WM deterioration has a much stronger influence on secondary degeneration. Through these findings, we demonstrate the potential contribution of myelin loss on neuronal degeneration at different disease stages and the usefulness of our statistical reduction technique which is not affected by the typical bias associated with approaches based on lesion masks.